Analysis of pesticides in surface water, stemflow, and throughfall in an agricultural area in South Georgia, USA. (October 2018) - Glinski, Donna A.; Purucker, S. Thomas; Van Meter, Robin J.; Black, Marsha C.; Henderson, W. Matthew
Abstract: To study spray drift contributions to non-targeted habitats, pesticide concentrations in stemflow (water flowing down the trunk of a tree during a rain event), throughfall (water from tree canopy only), and surface water in an agriculturally impacted wetland area near Tifton, Georgia, USA were measured (2015–2016). Agricultural fields and sampling locations were on the University of Georgia's Gibbs Research Farm, Tifton, GA. Samples were screened for more than 160 pesticides, and cumulatively, 32 different pesticides were detected across matrices. Data indicate that herbicides and fungicides were present in all types of environmental samples analyzed while insecticides were only detected in surface water samples. The highest pesticide concentration observed was 10.50 μg/L of metolachlor in an August 2015 surface water sample. Metolachlor, tebuconazole, and fipronil were the most frequently detected herbicide, fungicide, and insecticide, respectively, regardless of sample origin. The most frequently detected pesticide in surface water and stemflow samples was metolachlor (0.09–10.5 μg/L), however, the most commonly detected pesticide in throughfall samples was biphenyl (0.02–0.07 μg/L). These data help determine the importance of indirect chemical exposures to non-targeted habitats by assessing inputs from stemflow and throughfall into surface waters. Graphical abstract: Image 1 Highlights: Pesticide concentrations in surface water, stemflow and throughfall were analyzed. Metolachlor and tebuconazole were the most frequently detected pesticides. Higher concentrations were observed in throughfall compared to stemflow samples. Understanding migration of pesticides will help estimate risk to non-target species.